(untitled) (Applied Biological Research, 2016)
A study was conducted to assess genotypic variations in 10 green gram genotypes for root nodulation, root infection to Piriformospora indica, seed yield and N and P uptake. Rhizobium sp. strain-MB-703, P. indica and their combination were inoculated to green gram seeds. Significant genotypic differences observed for all the characters studied indicated the presence of considerable variability. All themicrobial treatments and genotype x microbial interaction differed significantly implying that the genotypes interacted differently with different microbial treatments. The traits affected by Rhizobium inoculation in most genotypes were nodules (number and dry weight), N content in seeds and seed yield. Rhizobium inoculation increased seed yield by 3.7-13.9% in genotypes MH-421, MH-810, MH-805, MH-560, MH-721 and MH-318. P. indica infection in roots was >50% in 8 genotypes and it caused increase in seed yield (3.7-6.3%) only in 5 genotypes viz., MH-560, Sattya, Basanti, MH 721 and MH-810. Dual inoculation caused 4.6-11.7% increase in seed yield in genotypes MH-421, Sattya, MH-810, MH-805, MH-318 and MH